PELATIHAN PEMBUATAN WADAH BERTEKSTUR ALAM MELALUI TEKNIK PRINTING UNTUK BINAAN RPTRA DHARMA SUCI, PLUIT - Henny Hidajat; Aprilia K.Streit; Ika Resmika Andelina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
In order to boost creativity, imagination, color recognition and nature sensitivity ofÂ children educated at RPTRA Dharma Suci, Pluit, as well as improving ideas to develop working program for its officers, DKV Faculty of Bunda Mulia University held a workshop